2021
DOI: 10.1186/s13045-021-01129-8
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine methyltransferases: functions, regulation, and clinical potential

Abstract: N6-methyladenosine (m6A) has emerged as an abundant modification throughout the transcriptome with widespread functions in protein-coding and noncoding RNAs. It affects the fates of modified RNAs, including their stability, splicing, and/or translation, and thus plays important roles in posttranscriptional regulation. To date, m6A methyltransferases have been reported to execute m6A deposition on distinct RNAs by their own or forming different complexes with additional partner proteins. In this review, we summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(98 citation statements)
references
References 165 publications
0
84
0
Order By: Relevance
“…N6-methyladenosine (m 6 A) is the most common internal modification in eukaryotic mRNA [4] . It is dynamically installed and removed, and acts as a new layer of mRNA fate, involving in m 6 A methyltransferase, demethylase and binding protein [5] , [6] , [7] . m 6 A binding protein, known as “reader”, is capable of decoding m 6 A methylation and yielding a series of functional signals, mainly including YTH domain containing protein, IGF2BP and HNRNP families [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…N6-methyladenosine (m 6 A) is the most common internal modification in eukaryotic mRNA [4] . It is dynamically installed and removed, and acts as a new layer of mRNA fate, involving in m 6 A methyltransferase, demethylase and binding protein [5] , [6] , [7] . m 6 A binding protein, known as “reader”, is capable of decoding m 6 A methylation and yielding a series of functional signals, mainly including YTH domain containing protein, IGF2BP and HNRNP families [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The key role of m6A modification mediated regulators in modulating DNA repair and genome stability has gradually attracted attention (38). Some m6A methyltransferases can modify and regulate the levels of RNAs involved in DNA damage and repair, which in turn affect genomic instability (39). For example, the m6A methyltransferase METTL3 is activated by ATMmediated phosphorylation and localized to DNA damage sites, where it promotes HRD repair (40).…”
Section: Discussionmentioning
confidence: 99%
“…N6-methyladenosine (m6A) is one of the most common internal transcription modifications in eukaryotic messenger RNA (mRNA) ( Huang et al, 2021 ; Oerum et al, 2021 ). The molecule was first identified in the 1970s, but recent studies have shown that m6A-associated mutations are closely related to BC occurrence ( Liu et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%